Reply to Commentaries and Future Directions - Pereira, Alfredo [UNESP] (Imprint Academic, 2021)
Here I summarize the theory of consciousness that is proposed in the target taper and that is translated there into various implications for medical practice, and then I go on to reply to each commentary on, and criticism of, both the theory and its translation. The criticisms are mostly based on the understanding that I equate sentience and homeostasis, and that I propose two fundamentally different types of consciousness. In reply, I explain that sentience is not homeostasis but a capacity of the system that drives the process (allostasis) of recovery of stability, after a stimulation that moves the system away from the homeostatic equilibrium zone. I also call attention to the temporally continuous nature of the process connecting sentience to consciousness, where 'anoetic consciousness' is the most immediate expression of the sentient capacity in conscious experience, as also manifested in non-human animals and possibly plants. Building on the theory and discussion, I sketch future directions, pointing to the opportunity of developing sentiomics, the science of the universal patterns of sentience, as distinct from qualiomics, the study of qualitative subjective features of first-person conscious experiences.
Keywords: homeostasis; control; allostasis; sentience; consciousness; cognition